Hydrophobic anticorrosive composite coating and preparation method thereof

By using biomass modified hollow glass microspheres and silane coupling agents, a hydrophobic and anti-corrosion composite coating was prepared, which solved the problem of the existing polyurea coating being easily corroded in an acidic environment, achieved excellent anti-corrosion and hydrophobic properties, and improved the environmental friendliness of the coating.

CN119592193AInactive Publication Date: 2025-03-11JIANGSU LANLING POLYMER MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411729955.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing polyurea coatings are prone to corrosion in acidic environments, which limits their application range, and metal powder fillers affect the dispersion and accumulation of coatings.

Method used

Biomass modified hollow glass microspheres are used as fillers, and their binding force with biomass is enhanced by etching treatment. Combined with silane coupling agent and additives, a hydrophobic and anti-corrosion composite coating is prepared.

Benefits of technology

The anticorrosion and excellent hydrophobic properties of composite coatings in acidic environments are achieved, while improving the environmental friendliness and performance stability of the coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005160033710000011
    Figure BDA0005160033710000011
  • Figure BDA0005160033710000051
    Figure BDA0005160033710000051
  • Figure FDA0005160033700000011
    Figure FDA0005160033700000011
Patent Text Reader

Abstract

The invention relates to the field of coatings, in particular to a hydrophobic anticorrosive composite coating and a preparation method thereof. The hydrophobic anticorrosive composite coating comprises the following components in parts by weight: 20-40 parts of isocyanate; 60 to 80 parts of polyether polyol; 10 to 20 parts of fluorine-containing polyol; 5-8 parts of a silane coupling agent; 6-10 parts of modified hollow glass microspheres; 2-5 parts of an auxiliary agent; according to the invention, biomass modified hollow glass microspheres are used as a filler, so that the composite coating has excellent hydrophobic and anticorrosive properties and also has the characteristic of environmental friendliness; grooves are formed in the surfaces of the modified hollow glass microspheres, so that the binding force between the modified hollow glass microspheres and the biomass is enhanced, and the biomass not only improves the dispersion of the modified hollow glass microspheres in a matrix, but also enhances the corrosion resistance of the composite coating; the preparation method disclosed by the invention is simple to operate, the etching treatment of the modified hollow glass microspheres is mild, and the surfaces of the hollow glass microspheres are not easy to damage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coatings, and in particular to a hydrophobic and anticorrosive composite coating and a preparation method thereof. Background Art

[0002] With the continuous advancement of China's industrialization and urbanization, it has provided an opportunity for the rapid development of industrial coatings, architectural coatings, etc., and the technical level of the coatings industry has improved rapidly. The surface of metal materials is easily affected by the natural environment and rusts, reducing its service life. In order to effectively prevent this from happening, applying protective coatings to the surface of steel and metal is an effective means. At present, protective coatings mainly include polyurethane waterproof coatings, acrylic waterproof coatings, polymer cement waterproof coatings, polyurea waterproof coatings, etc. With consumers' increasingly higher requirements for the safety and quality of coatings, polyurea coatings have attracted much attention due to their rapid curing, water resistance, excellent mechanical properties and chemical durability. In order to improve the performance of conventional polyurea coatings, metal powders are often added as fillers during the preparation process. However, metal powder fillers not only affect their dispersion and accumulation in the matrix, but are also easily affected by the environment and easily corroded by acid, which limits their application in acidic environments. Summary of the invention

[0003] The object of the present invention is to provide a hydrophobic and anti-corrosion composite coating and a preparation method thereof in view of the deficiencies in the prior art.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] The first aspect of the present invention is to provide a hydrophobic and anticorrosive composite coating, which comprises, by weight:

[0006]

[0007] Preferably, the silane coupling agent includes at least one of mercaptosilane, aminosilane, castor oil-modified silane coupling agent, and aniline propyltrimethoxysilane.

[0008] Preferably, the modified hollow glass microspheres are biomass-modified hollow glass microspheres, and the biomass includes at least one of chitosan, lignin, and cellulose.

[0009] Preferably, the auxiliary agent includes at least one of a curing agent, a defoaming agent, a leveling agent and an antioxidant.

[0010] The second aspect of the present invention is to provide a method for preparing the above-mentioned composite coating, the steps comprising:

[0011] S1. Weigh isocyanate, polyether polyol and fluorine-containing polyol in parts by weight, add them into a preheated reactor to react, and obtain a prepolymer;

[0012] S2. Weigh the silane coupling agent, modified hollow glass microspheres and auxiliary agents according to their weight, disperse the modified hollow glass microspheres in the silane coupling agent by ultrasonic, put them into a reaction kettle, then add the auxiliary agents and stir to obtain the composite coating.

[0013] Preferably, in step S1, the preheating treatment comprises: heating to 50-60°C at a heating rate of 4-6°C / min, and then keeping the temperature for 0.5-1h.

[0014] Preferably, in step S1, the reaction comprises: after isocyanate, polyether polyol and fluorine-containing polyol are put into a reactor, the reactor is heated to 70-80°C at a heating rate of 3-5°C, and the mixed components in the reactor are continuously stirred for 2-4h while heating.

[0015] Preferably, in step S2, the method for preparing the modified hollow glass microspheres comprises:

[0016] A1. Place the hollow glass microspheres in an alkali solution, stir for 20-40 minutes at room temperature, and then wash with deionized water for 2-5 times; place the washed hollow glass microspheres in an etchant, stir for 10-20 minutes in a 50-60°C water bath, and then wash with deionized water for several times until the pH is 7, thereby obtaining hollow glass microspheres with grooves on the surface;

[0017] A2. After the biomass and acetic acid solution are mixed and stirred evenly, hollow glass microspheres with grooves on the surface are added, stirred at 200-300 rpm for 20-40 min at 40-50° C., and then placed in a drying oven at 90-120° C. for 6-10 h to obtain the modified hollow glass microspheres.

[0018] More preferably, the etchant is ammonium fluoride.

[0019] Preferably, in step S2, the ultrasonic dispersion is carried out for 1-2 hours at a temperature of 40-50°C.

[0020] Preferably, in step S2, the stirring speed of the stirring treatment is 150-200 rpm, and the stirring time is 1-2 h.

[0021] The present invention adopts the above technical solution, and has the following technical effects compared with the prior art:

[0022] The present invention adopts biomass-modified hollow glass microspheres as fillers, so that the composite coating has excellent hydrophobic and anti-corrosion properties and is environmentally friendly; the surface of the modified hollow glass microspheres has grooves, which enhances the binding force between the modified hollow glass microspheres and the biomass, and the biomass not only improves the dispersion of the modified hollow glass microspheres in the matrix, but also enhances the anti-corrosion property of the composite coating; the preparation method of the present invention is simple to operate, and the etching treatment of the modified hollow glass microspheres is mild, and the surface of the hollow glass microspheres is not easily damaged. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0025] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.

[0026] Example 1

[0027] This embodiment provides a method for preparing a hydrophobic anticorrosive coating, the steps comprising:

[0028] S1. Weigh 25 parts of isocyanate, 60 parts of polyether polyol and 10 parts of fluorine-containing polyol by weight, heat the reactor to 51°C at a heating rate of 4°C / min, and keep it warm for 1h for preheating treatment. Add isocyanate, polyether polyol and fluorine-containing polyol to the preheated reactor, heat the reactor to 70°C at a heating rate of 3°C, and stir the mixed components in the reactor for 4h while heating to obtain a prepolymer;

[0029] S2, weighing 8 parts of castor oil modified silane coupling agent, 6 parts of chitosan modified hollow glass microspheres, 2 parts of curing agent, 1 part of leveling agent and 1 part of antioxidant by weight, dispersing the chitosan modified hollow glass microspheres in the castor oil modified silane coupling agent by ultrasonication at 50° C. for 1 h, putting the mixture into a reaction kettle, then adding the curing agent, leveling agent and antioxidant in sequence, stirring at 200 rpm for 1 h, to obtain the composite coating;

[0030] Wherein, the preparation method of the chitosan modified hollow glass microspheres comprises:

[0031] A1. Place the hollow glass microspheres in an alkali solution, stir for 30 minutes at room temperature, and then wash them with deionized water for 4 times; place the washed hollow glass microspheres in ammonium fluoride, stir for 10 minutes in a 60°C water bath, and then wash them with deionized water for several times until the pH is 7, thereby obtaining hollow glass microspheres with grooves on the surface;

[0032] A2. After chitosan and acetic acid solution are mixed and stirred evenly, hollow glass microspheres with grooves on the surface are added, stirred at 200 rpm for 40 min at 50° C., and then placed in a drying oven at 120° C. for 7 h to obtain the modified hollow glass microspheres.

[0033] Example 2

[0034] This embodiment provides another method for preparing a hydrophobic anticorrosive coating, the steps comprising:

[0035] S1. Weigh 38 parts of isocyanate, 75 parts of polyether polyol and 14 parts of fluorine-containing polyol by weight, heat the reactor to 60°C at a heating rate of 5°C / min, and keep it warm for 0.5h for preheating treatment. Add isocyanate, polyether polyol and fluorine-containing polyol to the preheated reactor, heat the reactor to 80°C at a heating rate of 4°C, and stir the mixed components in the reactor for 2h while heating to obtain a prepolymer;

[0036] S2, weighing 5 parts of aminosilane, 6 parts of lignin-modified hollow glass microspheres, 1 part of curing agent and 1 part of antioxidant by weight, dispersing the lignin-modified hollow glass microspheres in the aminosilane by ultrasonication at 50° C. for 1 h, putting them into a reactor, then adding the curing agent and antioxidant in sequence, stirring at 200 rpm for 1 h, to obtain the composite coating;

[0037] The preparation method of the lignin-modified hollow glass microspheres comprises:

[0038] A1. Place the hollow glass microspheres in an alkali solution, stir for 20 minutes at room temperature, and then wash them with deionized water for 4 times; place the washed hollow glass microspheres in ammonium fluoride, stir for 15 minutes in a 50°C water bath, and then wash them with deionized water for several times until the pH is 7, thereby obtaining hollow glass microspheres with grooves on the surface;

[0039] A2. After mixing sodium lignin sulfonate and acetic acid solution and stirring evenly, add hollow glass microspheres with grooves on the surface, stir at 300 rpm at 40° C. for 20 min, place in a drying oven at 100° C. for 10 h, and obtain the modified hollow glass microspheres.

[0040] Example 3

[0041] This embodiment provides another method for preparing a hydrophobic anticorrosive coating, the steps comprising:

[0042] S1. Weigh 20 parts of isocyanate, 78 parts of polyether polyol and 19 parts of fluorine-containing polyol by weight, heat the reactor to 55°C at a heating rate of 6°C / min, and keep it warm for 1 hour for preheating treatment. Add isocyanate, polyether polyol and fluorine-containing polyol to the preheated reactor, heat the reactor to 75°C at a heating rate of 5°C, and stir the mixed components in the reactor for 3 hours while heating to obtain a prepolymer;

[0043] S2, weighing 3 parts of castor oil-modified silane coupling agent, 2 parts of aniline propyl trimethoxy silane, 6 parts of lignin-modified hollow glass microspheres, 1 part of curing agent, 0.5 parts of defoaming agent and 1 part of leveling agent by weight, dispersing the lignin-modified hollow glass microspheres in aminosilane by ultrasonic at 50° C. for 1 h, putting them into a reactor, then adding the curing agent and antioxidant in sequence, stirring at 200 rpm for 1 h, and obtaining the composite coating;

[0044] The preparation method of the lignin-modified hollow glass microspheres comprises:

[0045] A1. Place the hollow glass microspheres in an alkali solution, stir for 30 minutes at room temperature, and then wash them with deionized water for 4 times; place the washed hollow glass microspheres in ammonium fluoride, stir for 10 minutes in a 60°C water bath, and then wash them with deionized water for several times until the pH is 7, thereby obtaining hollow glass microspheres with grooves on the surface;

[0046] A2. After mixing sodium lignin sulfonate and acetic acid solution and stirring evenly, add hollow glass microspheres with grooves on the surface, stir at 300 rpm for 30 min at 50° C., place in a drying oven at 90° C. for 10 h to obtain the modified hollow glass microspheres.

[0047] Comparative Example 1

[0048] This comparative example provides another method for preparing a coating, wherein unmodified hollow glass microspheres are used in step S2, and the rest are the same as in Example 1.

[0049] Comparative Example 2

[0050] This comparative example provides another method for preparing a coating. In step S2, modified hollow glass microspheres without grooves on the surface are used, and the rest are the same as in Example 1.

[0051] Detection Example

[0052] The coatings prepared by the preparation methods described in Examples 1-3 and Comparative Examples 1-2 and commercially available coatings were respectively applied on metal plates, and after heat curing at 70° C. for 3 hours, their appearance, hydrophobicity, corrosion resistance and adhesion were tested; the test results are shown in Table 1;

[0053] Table 1

[0054]

[0055]

[0056] Comparative Example 1 uses unmodified hollow glass microspheres. The interface compatibility between the unmodified hollow glass microspheres and the components in the coating is poor, and the interface bonding strength is weak, which causes the unmodified hollow glass microspheres to easily agglomerate in the coating and be difficult to disperse evenly, thereby affecting the coating performance; although Comparative Example 2 is modified, the surface of the hollow glass microspheres in Comparative Example 2 has no grooves. When modified, the biomass is not tightly bonded to the surface of the hollow glass microspheres, which still affects the performance of the coating to a certain extent; the present invention etches the hollow glass microspheres and then modifies them, so that the hollow glass microspheres are more tightly bonded to the biomass, thereby improving the various performances of the coating.

[0057] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.

Claims

1. A hydrophobic and anticorrosive composite coating, characterized in that: By weight, the components include:

2. The composite coating according to claim 1, characterized in that: The silane coupling agent comprises at least one of mercaptosilane, aminosilane, castor oil modified silane coupling agent and aniline propyl trimethoxy silane.

3. The composite coating according to claim 1, characterized in that: The modified hollow glass microspheres are biomass-modified hollow glass microspheres, and the biomass includes at least one of chitosan, lignin, and cellulose.

4. The composite coating according to claim 1, characterized in that: The auxiliary agent includes at least one of a curing agent, a defoaming agent, a leveling agent and an antioxidant.

5. A method for preparing a composite coating according to any one of claims 1 to 4, characterized in that the steps include: S1. Weigh isocyanate, polyether polyol and fluorine-containing polyol in parts by weight, add them into a preheated reactor to react, and obtain a prepolymer; S2. Weigh the silane coupling agent, modified hollow glass microspheres and auxiliary agents according to their weight, disperse the modified hollow glass microspheres in the silane coupling agent by ultrasonic, put them into a reaction kettle, then add the auxiliary agents and stir to obtain the composite coating.

6. The preparation method according to claim 5, characterized in that: In step S1, the preheating treatment includes: heating to 50-60°C at a heating rate of 4-6°C / min, and then keeping the temperature for 0.5-1h.

7. The preparation method according to claim 5, characterized in that: In step S1, the reaction includes: after isocyanate, polyether polyol and fluorine-containing polyol are put into a reactor, the reactor is heated to 70-80° C. at a heating rate of 3-5° C., and the mixed components in the reactor are stirred for 2-4 hours while heating.

8. The preparation method according to claim 5, characterized in that: In step S2, the method for preparing the modified hollow glass microspheres comprises: A1. Place the hollow glass microspheres in an alkali solution, stir for 20-40 minutes at room temperature, and then wash with deionized water for 2-5 times; place the washed hollow glass microspheres in an etchant, stir for 10-20 minutes in a 50-60°C water bath, and then wash with deionized water for several times until the pH is 7, thereby obtaining hollow glass microspheres with grooves on the surface; A2. After the biomass and acetic acid solution are mixed and stirred evenly, hollow glass microspheres with grooves on the surface are added, stirred at 200-300 rpm for 20-40 min at 40-50° C., and then placed in a drying oven at 90-120° C. for 6-10 h to obtain the modified hollow glass microspheres.

9. The preparation method according to claim 5, characterized in that: In step S2, the ultrasonic dispersion is carried out for 1-2 hours at a temperature of 40-50°C.

10. The preparation method according to claim 5, characterized in that: In step S2, the stirring speed of the stirring treatment is 150-200 rpm, and the stirring time is 1-2 h.